Kinetics of Palm Oil Transesterification in Methanol with Potassium Hydroxide as a Catalyst=Kinetika Transesterifikasi Minyak Sawit dengan Metanol Menggunakan Katalis Kalium Hidroksida - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2008)
A Study on palm oil transesterification to evaluate the effect of some parameters in the reaction on the reaction kinetics has been carried out. Transesterification was strated by preparing potassium methoxide from potassium hydroxide and methanol and then mixed it with the palm oil.